Strangers in the Dark: Navigating opacity and transparency in open online career-related knowledge sharing. Issue 1 (January 2023) - Vaast, Emmanuelle
Given repeated upheavals in jobs and organizations, people increasingly share career-related knowledge in open online platforms. Dealing with career-related knowledge in an open online setting, though, is challenging. It requires people to balance between exchanging too much and too little career-related knowledge, e.g., to disclose and share the right knowledge without jeopardizing themselves. This study examines how participants achieve such delicate balance in open online processes. It investigates discussions in a career advice-focused online platform. Findings reveal how open online career-related exchanges include sequences of knowledge sharing, knowledge evaluating, and of diverting. They also include sequences of regulating openness that involve securing opacity for the people participating while also ensuring the transparency of the process. The study unpacks how participants in an open online setting navigate the dynamic balance between individual opacity and processual transparency. Findings hold implications for scholarship on open organizing, careers, and advice networks, as well as for practice.